Antibioticoprofilaxia pós-operatória em mamoplastia redutora: ensaio clínico com randomização - Garcia, Edgard da Silva [UNIFESP] (2018)
Introduction: Reduction mammoplasty is a routine and well-established procedure. Studies have shown benefits of using antibiotics in this procedure. Nevertheless, there is no evidence to support postoperative antibiotic prophylaxis. Objective: Evaluating the influence of postoperative antibiotics delivery on infection rates after reduction mammoplasties. Methods: Randomized trial of non-inferiority, with two parallel groups, triple blinding. The participants were 124 women with breast hypertrophy, with reduction mammoplasty already scheduled, selected consecutively. All the patients underwent reduction mammoplasty, by the same surgical team, using the super-medial pedicle technique for ascending the nipple-areola complex. All patients received cephalothin (1g) intravenously at the anesthetic induction and every six hours for 24 hours. At hospital discharge, they were randomly assigned to the placebo (PG, n = 62) or antibiotic (AG, n = 62) group and were instructed to take identical capsules containing 500mg cephalexin or placebo, respectively, every six hours for seven days. The patients were weekly seen for the occurrence of surgical site infection, using the criteria and definitions of the Centers for Disease Control and Prevention, for 30 days, by a surgeon who was unaware of the allocation. Results: There was no statistical difference between groups regarding age, body mass index or resected breast tissue weight. The overall surgical site infection rate was 0.81%. Only one patient, allocated to AG, presented infection, classified as superficial incision (p=1.00). In AG, surgery time was higher (p=0.003). Conclusion: The maintenance of antibiotics in the postoperative period of reducing mammoplasties did not influence the rates of surgical site infection.